Effect of co-substitution of Co2+ and V5+ for Fe3+ on the magnetic properties of CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Physica B: Condensed Matter, 2019)
Different chemical compositions in Co1+2xVxFe2-3xO4 (0 ≤ x ≤ 0.1) have been synthesized by the conventional solid-state reaction method and processed under identical conditions. The materials are investigated to assess the impact of change in the oxidation states of metal ions on structural and magnetic properties of cobalt ferrite. Rietveld refinement of the X-ray diffraction patterns revealed a single phase nature of all compositions with cubic spinel structure. The cubic lattice parameter was found to decrease non-linearly from 8.393 Å for x = 0 to 8.377 Å for x = 0.1, due to the effect of ionic size and valency of the substituted metal ions. Sintered co-substituted compositions exhibited smaller grains against unsubstituted counterpart, due to low melting point of raw material V2O5. Strong experimental evidence of V substitution for Fe at the tetrahedral sites of the spinel ferrite has been extracted from the Raman spectral analysis. Saturation magnetization (Ms) was observed to decrease from 452 kA/m for x = 0–411 kA/m for x = 0.1. Coercivity (Hc) and magnetocrystalline anisotropy (K1) were also found to follow the same trend. Variation of the structural and magnetic parameters is attributed to the changes in the oxidation state of Co from 2 + to 3 + as it is confirmed from the results of XPS analysis.